KAJIAN YURIDIS TERHADAP PENEGAKAN HUKUM DALAM KASUS PENCABULAN ANAK OLEH PENDIDIK : STUDI PUTUSAN PENGADILAN NEGERI SIDOARJO NOMOR 203/PID.SUS/2021/PN SDA - Sejati, Latu Rangga Mito (Gapenas Publisher, 2025)
This research aims to analyze law enforcement in cases of child molestation by educators, with a specific study on the Decision of the District Court of Sidoarjo Number 203/Pid.Sus/2021/PN Sda. The research method applied is normative legal research with a case approach and a statutory approach. The results indicate that judges, in rendering decisions, consider not only juridical aspects but also philosophical, sociological, and psychological aspects in order to realize justice, legal certainty, and legal benefit. The conclusion emphasizes that legal protection for children who are victims of molestation by educators still requires stronger regulations, consistent law enforcement, and more comprehensive preventive policies